2016
DOI: 10.18280/ijht.34sp0243
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of a Solar Electric Driven Heat Pump for an Office Building Located in Southern Italy

Abstract: The paper investigates the introduction of a solar electric driven heat pump for an office building, placed in southern Italy, with low energy demand in comparison with the most common type of Italian buildings. Dynamic simulations to evaluate energy, environmental and economic performance of the proposed system, varying photovoltaic peak powers (4500 W -7500 W), tilt angles (20° -50°), electricity and natural gas unit prices, are carried out. To meet heating and cooling demand a heat pump driven by electricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For hot water and space heating, both evacuated tube collectors (ETC) and flat plate collectors (FPC) are adopted. In the plant of solar-HP hybrid technologies for buildings, a solar system for heating and cooling, based on a PV combined to an HP was proposed to match the energy demand of an office in Southern Italy [14]. Dynamic simulations were performed to analyze the energy, environment and economics at different technical and economical parameters that included the tilt angle, peak power of PV, electricity price and natural gas price.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hot water and space heating, both evacuated tube collectors (ETC) and flat plate collectors (FPC) are adopted. In the plant of solar-HP hybrid technologies for buildings, a solar system for heating and cooling, based on a PV combined to an HP was proposed to match the energy demand of an office in Southern Italy [14]. Dynamic simulations were performed to analyze the energy, environment and economics at different technical and economical parameters that included the tilt angle, peak power of PV, electricity price and natural gas price.…”
Section: Introductionmentioning
confidence: 99%
“…This option based on solar energy integration reported a primary energy savings of 81% due the reduction of fossil fuel consumption and equivalent CO2 emission when compared to a conventional natural gas boiler and an electric-driven chiller. In addition, the same research [14] compared the performance of solar thermal and solar electrical cooling systems in two different European countries (Germany and Spain) for a residential building, reporting an expected primary energy savings of up to 40% for Germany's building and up to 60% for Spain's building both for the STC collectors and PV modules. To fulfill the demand of an office building for space heating and cooling, a PV-driven heat pump equipped with a battery storage system was considered in Reference [15], analyzing the thermo-economic performances at different peak powers of PV and the battery capacity by means of TRNSYS.…”
Section: Introductionmentioning
confidence: 99%
“…Roselli et al investigated a solar electric-driven heat pump for an office building located in southern Italy, which resulted in low energy demand compared to the most common type of Italian buildings [9]. It was found that the system based on the solar electric-driven heat pump resulted in a saving of primary energy and equivalent CO 2 emission reduction of about 81% when compared to the reference conventional system based on a boiler fueled by natural gas and an electric-driven chiller.…”
Section: Introductionmentioning
confidence: 99%
“…Solar electric heating and cooling plant based on a PV plant and an EHP [12] satisfying electric, thermal and cooling demand of an office building located in southern Italy was analyzed. Dynamic simulations to evaluate energy, environmental and economic performance of the proposed system, varying PV peak powers, tilt angles, electricity and natural gas unit prices, are carried out by means of TRNSYS software.…”
Section: Introductionmentioning
confidence: 99%